Anticoagulant interventions in hospitalized patients with COVID‐19: A scoping review of randomized controlled trials and call for international collaboration. (1st October 2020) - Tritschler, Tobias; Mathieu, Marie‐Eve; Skeith, Leslie; Rodger, Marc; Middeldorp, Saskia; Brighton, Timothy; Sandset, Per Morten; Kahn, Susan R.; Angus, Derek C.; Blondon, Marc; Bonten, Marc J.; Cattaneo, Marco; et al.
Abstract: Introduction: Coronavirus disease (COVID‐19) is associated with a high incidence of thrombosis and mortality despite standard anticoagulant thromboprophylaxis. There is equipoise regarding the optimal dose of anticoagulant intervention in hospitalized patients with COVID‐19 and consequently, immediate answers from high‐quality randomized trials are needed. Methods: The World Health Organization's International Clinical Trials Registry Platform was searched on June 17, 2020 for randomized controlled trials comparing increased dose to standard dose anticoagulant interventions in hospitalized COVID‐19 patients. Two authors independently screened the full records for eligibility and extracted data in duplicate. Results: A total of 20 trials were included in the review. All trials are open label, 5 trials use an adaptive design, 1 trial uses a factorial design, 2 trials combine multi‐arm parallel group and factorial designs in flexible platform trials, and at least 15 trials have multiple study sites. With individual target sample sizes ranging from 30 to 3000 participants, the pooled sample size of all included trials is 12 568 participants. Two trials include only intensive care unit patients, and 10 trials base patient eligibility on elevated D‐dimer levels. Therapeutic intensity anticoagulation is evaluated in 14 trials. All‐cause mortality is part of the primary outcome in 14 trials. Discussion: Several trials evaluate different dose regimens of anticoagulant interventions in hospitalized patients with COVID‐19. Because these trials compete for sites and study participants, a collaborative effort is needed to complete trials faster, conduct pooled analyses and bring effective interventions to patients more quickly.